2012
DOI: 10.1371/journal.pone.0051565
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Analyses of Shiga Toxin-Producing Escherichia coli O157 and Non-O157 Recovered from Feces of Domestic Animals on Rural Farms in Mexico

Abstract: Shiga toxin-producing Escherichia coli (STEC) are zoonotic enteric pathogens associated with human gastroenteritis worldwide. Cattle and small ruminants are important animal reservoirs of STEC. The present study investigated animal reservoirs for STEC in small rural farms in the Culiacan Valley, an important agricultural region located in Northwest Mexico. A total of 240 fecal samples from domestic animals were collected from five sampling sites in the Culiacan Valley and were subjected to an enrichment protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 67 publications
(97 reference statements)
3
49
1
1
Order By: Relevance
“…Isolates with PFGE patterns H, C, E, and M all had the stx 1 , stx 2 , ehxA and eaeA genotype. However, E. coli O157:H7 isolates with the other PFGE patterns possessed a variety of genotypes, such as stx 1 , stx 2 and eaeA (A and I); stx 1 , stx 2 and ehxA (B, D, F and G); stx 1 and stx 2 (J) or stx 2 and eaeA (K and L)…”
Section: Pfge Profiles Of E Coli O157:h7 Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates with PFGE patterns H, C, E, and M all had the stx 1 , stx 2 , ehxA and eaeA genotype. However, E. coli O157:H7 isolates with the other PFGE patterns possessed a variety of genotypes, such as stx 1 , stx 2 and eaeA (A and I); stx 1 , stx 2 and ehxA (B, D, F and G); stx 1 and stx 2 (J) or stx 2 and eaeA (K and L)…”
Section: Pfge Profiles Of E Coli O157:h7 Isolatesmentioning
confidence: 99%
“…In humans, they can cause severe outbreaks of gastrointestinal illness with clinical symptoms ranging from diarrhea and hemorrhagic colitis to the life-threatening haemolytic uremic syndrome. 1 STEC strains causing human infections belong to a large number of O:H serotypes. Most outbreaks and sporadic cases of hemorrhagic colitis and haemolytic uremic syndrome (HUS) have been attributed to the STEC O157 strains; the H7 flagellum is frequently but not always present on O157 isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Although cattle are considered to be the major reservoir of STEC strains, sheep also represent important carriers of these pathogens, and higher prevalence of STEC have been detected in ovine feces (Mora et al, 2011;Amé zquita-Ló pez et al, 2012) and meat (Momtaz et al, 2013) when compared to samples of bovine origin. Nevertheless, only a few studies have reported the occurrence of STEC in Brazilian sheep populations (Vettorato et al, 2009;Maluta et al, 2014;Martins et al, 2014) and, particularly in the South region where approximately 30% of the national flock is found, these data are unknown so far.…”
Section: Introductionmentioning
confidence: 99%
“…The most important virulence factors include shiga toxins encoded by the stx1 and stx2 genes, intimin encoded by the eae gene and enterohaemorrhagic E. coli (EHEC) haemolysin encoded by the EHEChlyA gene (Sanchez et al 2010;Amezquita-Lopez et al 2012). Several molecular techniques have been used to determine the genotypes of human, food and animal E. coli isolates, and pulsed-field gel electrophoresis (PFGE) is considered the gold standard for molecular typing of STEC O157:H7 isolates (Liebana et al 2003).…”
mentioning
confidence: 99%